Salary and the Gender Salary Gap in the Academic Profession - Melanie E. Ward (Institute for the Study of Labor (IZA), 1999)
The academic profession is an occupation in which pay has fallen dramatically, resulting in the setting up of a Committee of Inquiry to examine both pay relativities and mechanisms for pay determination. This paper considers salary determination and the gender salary gap in the academic labour market drawing upon a particularly detailed data set of 900 academics from five traditional Scottish Universities. Results reveal an aggregate gender salary differential for academic staff of 15%. Most of this differential can, however, be explained by our model. Evidence suggests a limited opportunity for female academics to combine career and family, despite the flexibility of an academic job and emphasises the importance of mobility to the male career. Publication record, but not teaching ability, is found to be an important determinant of salary. The dominant contribution of rank to both the determination of female academic salaries and the gender salary gap suggests vastly differential opportunities for promotion faced by men and women.
Keywords: J44; 330; Academic labour market; salary; gender differences; Hochschullehrer; Wissenschaftler; Besoldung; Geschlecht; Erwerbsverlauf; Lohndifferenzierung; Familiensoziologie; Großbritannien; Schottland